Economic and Social Consequences of The Impact of The COVID–19 Pandemic on The Activities of The Cultural Sector: A Case Study For Poland - Katarzyna SZARA; Anna MAZURKIEWICZ (Communications of International Proceedings, 2021)
In order to combat the COVID-19 epidemic in 2020, governments worldwide have taken measures to prevent the spread of the coronavirus. Reduction of an economic activity has been one of the solutions. The closure of economies in many countries has also impeded activities in other spheres, including cultural and entertainment activities with participation of an audience. The aim of the paper is to identify the economic and social impact of the COVID-19 pandemic on the activities of the cultural sector in Poland. In order to achieve the goal, the method of critical analysis of the literature has been applied, using secondary data from the Central Statistical Office concerning the cultural sector since the announcement of the pandemic in Poland. Representatives of the cultural sector have changed the format and the scope of the projects implemented. Most of the activities have been moved to the virtual sphere. It required the employees of the culture sector to present the results of their work remotely. A decline in revenues in the culture sector caused by the suspension of operations has resulted in the lack of coverage of the costs of current operations and generated a loss. The impact of the pandemic has had economic consequences not only for all entities in the cultural sector, but also for their employees. The pandemic often deprived them of a job or an income, which translated into their social situation. The situation caused by the pandemic in Poland is similar to that in many European Union countries. The measures taken to counteract the effects of the pandemic are important due to the diversification of the cultural sector, so as to restore the activities of all cultural entities in the broadest possible form as soon as possible.
Keywords: Economic; Impact; COVID – 19; Cultural Sector